Frequency-Hopping Binary Offset Carrier Modulation with Independent Frequency-Hopping Patterns in Lower and Upper Sidebands - Yang, Yikang; Ma, Jiangang; Deng, Lingyu; Li, Hengnian (Remote sensing (Basel, Switzerland), 2024)
To enhance the anti-interference capabilities and increase flexibility in frequency allocation between the lower and upper sidebands of the navigation signal, we introduce frequency-hopping binary offset carrier modulation with independent frequency-hopping patterns in lower and upper sidebands (IFH-BOC). This novel modulation is classified as a constant-envelope multiplexing (CEM) method, with independent frequency-hopping patterns for the lower and upper sidebands, in contrast with frequency-hopping binary offset carrier (FH-BOC) and binary offset carrier (BOC) modulations, which share the same patterns. IFH-BOC represents a generalized modulation that incorporates FH-BOC and BOC, thus retaining their advantages while introducing new characteristics, such as independent frequency-hopping pattern design and flexible spectral splitting. The results indicate that IFH-BOC maintains the same time–frequency characteristics and measurement accuracy as FH-BOC when using identical modulation parameters, yet it demonstrates superior anti-interference performance due to its varied frequency-hopping patterns. Furthermore, IFH-BOC provides enhanced flexibility in spectral splitting compared with BOC modulation, potentially allowing for increased availability of L-band frequencies for satellite navigation. With these benefits, IFH-BOC is poised to be a promising modulation for the signal design of next-generation global navigation satellite systems.